Exfoliated NiFe Layered Double Hydroxide Cocatalyst for Enhanced Photoelectrochemical Water Oxidation with Hematite Photoanode. Issue 1 (28th November 2018) - Park, Yoon Bin; Kim, Ju Hun; Jang, Youn Jeong; Lee, Jin Ho; Lee, Min Hee; Lee, Byeong Jun; Youn, Duck Hyun; Lee, Jae Sung
Abstract: In photoelectrochemical (PEC) water oxidation, a low onset potential and a high photocurrent are desired and a cocatalyst on the photoanode could improve the performance. For better use of a NiFe layered double hydroxide (LDH) cocatalyst, concept of exfoliation is applied. Exfoliation gives higher electrochemical surface area and better water oxidation kinetics, which is reflected in improved charge injection efficiency at low bias potentials. Exfoliated NiFe LDH shows increased photocurrent density by 50 % at 1.0 VRHE and reduced onset potential by 140 mV relative to those of stacked bulk LDH under 1 sun illumination, making it a much more effective cocatalyst for α‐Fe2 O3 photoanode. The intensity modulated photocurrent spectroscopy shows that the improved photocurrents and early onset potentials of exfLDH/α‐Fe2 O3 photoanode are attributed to fast charge transfer and, more importantly, suppressed charge recombination due to passivation of α‐Fe2 O3 surface by the LDH monolayer sheet. Abstract : Double trouble catalysis : Exfoliated NiFe LDH accelerates photoelectrochemical water splitting as a cocatalyst for α‐Fe2 O3 more effectively than stacked LDH in terms of onset potential and photocurrent generation. The effects originate from fast charge transfer and suppressed charge recombination due to passivation of α‐Fe2 O3 surface by LDH monolayer sheet.